(untitled) (Asian Journal of Ethnobiology, 2022)
Abstract. Haile AA. 2022. Ethnobotanical study of medicinal plants used by local people of Mojana Wadera Woreda, North Shewa Zone, Amhara Region, Ethiopia. Asian J Ethnobiol 5: 35-43. This study was conducted in Mojana Wadera Woreda of North Shewa Zone (Ethiopia) to document the indigenous knowledge of local communities on medicinal plants. The data was collected using structured and semistructured interviews with herbalists. Information on medicinal plants was collected from June 2020 to October 2020. Fourteen (10 males and 4 females) key informants were deliberately selected during the data collection, but no group discussion was conducted due to the coronavirus epidemic. Descriptive statists (percentage and frequency) were used to summarize ethnobotanical data and preference ranking, and the Information consensus factor (ICF) was also included. A total of 56 medicinal plants from 52 genera, and 38 families, were identified in the study area, where they were used to treat human and animal diseases. Family-wise, Asteraceae was the most dominant family, followed by Lamiaceae. Herbs were the most dominant growth forms as they accounted for about 29 (52.72%) species, while shrubs had 17 (30.9%) species. Most herbal remedies were prepared by mixing 25.45% of the roots and leaves. The preparation was usually done by crushing to 45.45%, and during the preparation, the herbs were usually fresh. Most medicines were administered orally to the sick. According to the key informant’s response, the plants in the study area are under threat. Therefore, the conservation of medicinal plants related to indigenous knowledge is important for future generations.